Possible feed rate at filling gullets of saw teeth up with sawdust for horizontal band saw cutting - Shostak, Volodymyr; Puna, Volodymyr; Aсberger , Yosyp (Forestry, Forest, Paper and Woodworking Industry, 2024)
It is set that at the section of logs horizontal band saw, sawdusts fall downward on the surface of board and cuddle to her a saw. Formulas are resulted for the calculation of volume of the cut away shaving and volume of sawdusts falling out on the surface of board. The coefficient of form of indent of band saw is certain. Conducted the series of experiments for determination of actual correlation between the volume of falling out sawdusts and volume of the cut away shaving. It was carried out tests on a horizontal band saw machine-tool. Used a saw in 1,1 mm thick with the step of indents 22,2 mm. The size of divorce made 0,42 mm. Indents had a type of Wood Mizer type BW. A breed of wood is a pine-tree. Cutting speed was 34 m/s. Speed of serve was 2,6 m/min. Humidity of wood was 15 %. Changed a height drank away from 10 to 40 sm. Conducted 16 experiments. Sawdusts collected from a board after each drank away. It is set that an average of correlation was 22,1 %. Determined the coefficient of tension of cavities of indents of saw, as correlation of volume of sawdusts remaining in the cavity of indent to the volume of the cut away sawdusts. Got a formula for determination of possible speed of serve on filling of cavities sawdusts between indents. From this formula evidently, that with multiplying a height drank away coefficient of tension of cavities of indents, possible speed of serve diminishes on hyperbolical dependence Set that heating of band saw took place due to a friction after sawdusts, remaining on the walls of board. Resin sticks on a saw-blade. It results in a yet greater friction and heating. It is suggested to multiply a width drank away by a proppant device. To delete sawdusts with drank away by the saws of equipped the additional indents of bearing-outs. The results of theoretical and experimental studies have been considered. The coefficient of tooth shape of band saw and quantity of sawdust remained in kerf have been determined. Reasons for tool heating has been studied. Recommendation for providing stability of band saw body in kerf has been suggested as well.